Screening criteria for high-quality Glycyrrhiza uralensis Fisch. seeds from the Ordos Plateau - Dongyang Fang; Xinyang Zhao; Yuqing Pan; Jiaxin Qiao; Yongbin Xu; Erjun Chai; Yali Li (Scientific Reports)
Abstract In the standardized production of the herb Glycyrrhiza uralensis Fisch., high-quality seeds and seedlings serve as the basis of production and are the main precondition that ensures the quality of herbs produced from these sources. Using traditional seed quality testing methods such as the halving method, soaking method, hundred grain weight method, red ink dyeing method, electrical conductivity method, and high-temperature drying method, quality grading standards for G. uralensis seeds were formulated by determining indices, namely, the purity, morphology, thousand grain weight, hardness rate, germination rate, moisture content, viability, vigor, and health, of seeds circulating on the market on the Ordos Plateau with obvious differences in size and color of the seed coat. Based on the results, the following criteria were established: for first-grade seeds, small-seed thousand grain weight ≥ 6.7 g, large-seed thousand grain weight ≥ 12.2 g, purity ≥ 99%, hardness rate ≥ 85%, seed germination rate under normal growing conditions ≥ 85%, seed germination rate under drought stress ≥ 70%, moisture content ≤ 7%, viability ≥ 90%, conductivity ≤ 20 µS·(cm·g)−1, and smooth surface; and for second-grade seeds, small-seed thousand grain weight ≥ 4.6 g, large-seed thousand grain weight ≥ 11.8 g, purity ≥ 96%, hardness rate ≥ 50%, seed germination rate under normal growing conditions ≥ 30%, seed germination rate under drought stress ≥ 15%, moisture content ≤ 7%, viability ≥ 60%, conductivity ≤ 100 µS·(cm·g)−1, and smooth or slightly wrinkled surface. However, second-grade seeds have more than two unqualified indices, and therefore seeds that are less than first-grade are classed as failing screening. The quality grading standards developed for G. uralensis seeds can provide an experimental basis for analyzing the current status of G. uralensis seed quality and devising standard operating procedures for seed testing.